The genotoxic effects of fruit extract of Crataegus oxyacantha (hawthorn) in mice - Yonekubo, Bruna Thiemi [UNESP] (2018)
Crataegus oxyacantha L. (Rosaceae) is a medicinal plant with a long history of use in European, Chinese, and American. The majority of pharmacological activities associated with fruit extracts of C. oxyacantha L. are related to cardio-stimulant properties utilized in the treatment of atherosclerosis, hypertension with myocardic insufficiency, angina pectoris, cardiac rhythm alterations, and heart failure. Some other therapeutic uses for renal calculi, dyspnea, as well as a diuretic, sedative, and anxiolytic were also reported. Due to the beneficial potential of C. oxyacantha fruits extract but evidence in vitro of genetic toxicity, the aim of the present study was to examine the genotoxic potential of plant extract in vivo in mice. The extract was administered orally, daily by gavage at doses of 50, 100, and 200 mg/kg body weight for seven days. Data demonstrated that C. oxyacantha extract did not markedly induce DNA damage in leukocytes and bone marrow cells by the comet assay; however, the extract produced a significant rise in micronucleated polychromatic erythrocytes (PCE) at all tested doses in a non-dose dependent manner as evidenced by the micronucleus test. The PCE/normochromatic erythrocytes (NCE) ratio indicated no significant cytotoxicity. Under our experimental conditions, C. oxyacantha fruits extract exhibited weak clastogenic and/or aneugenic effects in bone marrow cells of male mice, confirming our previous in vitro findings that this plant extract induced genotoxicity suggesting that prolonged or high dose use needs to be undertaken with caution.